Brazilian privatization in the 1990s - Armando Castelar Pinheiro; Fabio Giambiagi (Institute for Applied Economic Research (ipea), 2015)
This paper makes a partial assessment of the Brazilian privatization program in the 1990s. The article focuses mainly on the fiscal impact of asset sales, which, we argue, has been relatively small. We conclude that the failure of the government's stabilization attempts has reduced the fiscal benefits of privatization, and inhibited the government's capacity to impose limits on buyers who have increased their market power through the acquisition of state-owned enterprises. In practice, the main objective of the privatization program has been to highlight the commitment to market-oriented reforms - in a certain sense, privatization has wound up creating its own logic, beyond its original objectives.
Keywords: 330